N6-Methyladenosine-Sculpted Regulatory Landscape of Noncoding RNA - Zhang, Zhongyuan; Wei, Wei; Wang, Hao; Dong, Jiangning (Frontiers in Oncology, 2021)
The exploration of dynamic N6-methyladenosine (m6A) RNA modification in mammalian cells has attracted great interest in recent years. M6A modification plays pivotal roles in multiple biological and pathological processes, including cellular reprogramming, fertility, senescence, and tumorigenesis. In comparison with growing research unraveling the effects of m6A modifications on eukaryotic messenger RNAs, reports of the association between noncoding RNAs and m6A modification are relatively limited. Noncoding RNAs that undergo m6A modification are capable of regulating gene expression and also play an important role in epigenetic regulation. Moreover, the homeostasis of m6A modification can be affected by noncoding RNAs across a broad spectrum of biological activities. Importantly, fine-tuning and interaction between these processes are responsible for cell development, as well as the initiation and progression of the disease. Hence, in this review, we provide an account of recent developments, revealing biological interactions between noncoding RNAs and m6A modification, and discuss the potential clinical applications of interfering with m6A modification.